Conducting Polymers in Solar Cells: Insights, Innovations, and Challenges - Aliya Yelshibay; Sherif Dei Bukari; Bakhytzhan Baptayev; Mannix P. Balanay (Organics, 2024)
The pursuit of sustainable energy sources has led to significant advances in solar cell technology, with conducting polymers (CPs) emerging as key innovations. This review examines how CPs improve the performance and versatility of three important types of solar cells: dye-sensitized solar cells (DSSCs), perovskite solar cells (PSCs), and organic solar cells (OSCs). Polymers such as polyaniline, polypyrrole, and poly(3,4-ethylenedioxythiophene) have shown significant potential to increase the efficiency of solar cells. In DSSCs, conducting polymers act as counter electrodes, electrolytes, and dyes, contributing to improved efficiency and stability. In PSCs, they serve as hole transport materials and electron transport materials that improve charge separation and reduce recombination losses. In OSCs, conducting polymers act as HTMs and active layers, significantly impacting device performance and enabling advances in both binary and ternary solar cell configurations. Recent research highlights the important role of conducting polymers in improving both the efficiency and stability of solar cells under different indoor and outdoor lighting conditions. Recent advances have led to impressive energy conversion efficiencies, particularly in low-light environments. This report also highlights the environmental and economic benefits associated with these materials. At the same time, it highlights the challenges associated with optimizing the materials, scalability, and ensuring long-term stability. Future research directions are outlined to overcome these obstacles and promote the commercial viability of next-generation solar technologies.